2017
DOI: 10.1109/tbcas.2016.2593639
|View full text |Cite
|
Sign up to set email alerts
|

Towards High Throughput Cell Growth Screening: A New CMOS 8 <inline-formula> <tex-math notation="LaTeX">$\times$</tex-math> </inline-formula> 8 Biosensor Array for Life Science Applications

Abstract: In this paper we present a CMOS capacitive sensor array as a compact and low-cost platform for high-throughput cell growth monitoring. The proposed biosensor, consists of an array of 8 × 8 CMOS fully differential charge-based capacitive measurement sensors. A DC-input Σ∆ modulator is used to convert the sensors' signals to digital values for reading out the biological/chemical data and further signal processing. To compensate the mismatch variations between the current mirror transistors, a calibration circuit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…LECTROCHEMICAL impedance spectroscopy (EIS) is a popular sensing technique, thanks to its capability to investigate different sample properties at different frequencies [1]. Miniaturization and monolithic integration of EIS sensors in CMOS technology is possible, enabling highly parallel sensing and readout [2] [13]. Within the field of capacitance biosensors [14], high sensitivity realizations have been presented, that enable the implementation of CMOS DNA sensor arrays [4] [15], and even F. Widdershoven is with NXP Semiconductors, Eindhoven, The Netherlands (e-mail: frans.widdershoven@nxp.com).…”
Section: Introductionmentioning
confidence: 99%
“…LECTROCHEMICAL impedance spectroscopy (EIS) is a popular sensing technique, thanks to its capability to investigate different sample properties at different frequencies [1]. Miniaturization and monolithic integration of EIS sensors in CMOS technology is possible, enabling highly parallel sensing and readout [2] [13]. Within the field of capacitance biosensors [14], high sensitivity realizations have been presented, that enable the implementation of CMOS DNA sensor arrays [4] [15], and even F. Widdershoven is with NXP Semiconductors, Eindhoven, The Netherlands (e-mail: frans.widdershoven@nxp.com).…”
Section: Introductionmentioning
confidence: 99%
“…Besides ISFET devices, classical MOSFETs have been described for the monitoring of cell detachment. For example, Nabovati et al [ 3 ] reported a capacitive sensor array using the CMOS technology for in-situ cell growth monitoring. They constructed an array of 8 × 8 CMOS that measured capacitance at the interface between the sensor and the cell culture medium.…”
Section: Devicesmentioning
confidence: 99%
“…Complex biological interactions or cellular stress responses difficult to highlight using conventional biosensors, can be identified because of the changes in cellular physiology. These changes are, typically, local changes in pH [ 1 , 2 ], in surface coverage of cells [ 3 , 4 , 5 , 6 ], in protein expression, or in cellular metabolism that induce local changes in the concentration of metabolites or biochemicals, such as glucose, lactate [ 7 , 8 ], dopamine [ 9 ], glutamate, acetylcholine, etc. Cell culture monitoring may also be applied to monitor cancer cells’ metabolism, for example.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of microelectromechanical systems (MEMS)-based capacitive sensors such as accelerometers [ 1 , 2 ], position sensors [ 3 , 4 ], pressure sensors [ 5 , 6 , 7 , 8 ], and moisture sensors [ 9 ], a growing body of literature has studied capacitive sensors for Laboratory on a Chip (LoC) applications. These applications include DNA hybridization detection [ 10 ], protein interactions quantification [ 11 ], cellular monitoring [ 12 , 13 , 14 ], bio-particle detection [ 15 ], microRNA detection [ 16 ], organic solvent monitoring [ 17 ], sensing of droplet parameters [ 18 ], and bacteria detection [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…A capacitive sensor consists of sensing electrodes that are connected to an interface readout circuit, as shown in Figure 1 a,b for both MEMS-based and LoC applications, respectively. The capacitive electrodes convert the physical [ 3 , 4 ], biological [ 10 , 11 , 12 ], and/or chemical parameters [ 21 , 22 ] in proximity of the electrodes into electrical signals. As illustrated in Figure 1 a, the capacitive electrodes in MEMS-based applications such as accelerometers are used as an off-chip device wire-bonded (or flip-chip bonded) to the CMOS chip.…”
Section: Introductionmentioning
confidence: 99%